Production of biosurfactant stabilized nanoparticles - POOJA SINGH; SELVAN RAVINDRAN; JITENDRA KUMAR SUTHAR; POOJA DESHPANDE; RUTUJA ROKADE; VINAYKUMAR RALE (International Journal of Pharma and Bio Sciences, 2017)
Biosurfactants belong to a well known class of microbial compounds possessing interfacial and biological activities as well as environment friendly characteristics. Recently extensive research work has been carried out by scientific community; and various novel applications of biosurfactants are being probed by industrial communities to a greater extent. This paper reviews one of the most recent applications of biosurfactants and synthesis of nanoparticles especially with respect to its application in the biomedical field. This review also emphasize the interdependent production of biosurfactants and nanoparticles.